Strategy for Teachers of Service in Forming Disciplinary Character and Responsibilities of Mahasantriwati Al-Amien Prenduan University - Rauhul Maani; Moh. Nasir (Interpersonal: Jurnal Bimbingan Konseling Islam, 2025)
Islamic boarding schools play an important role in shaping the character and personality of students, by instilling values of discipline and responsibility as part of moral and spiritual development. However, the reality in the field shows that some students are not fully disciplined and responsible in carrying out their obligations. At UNIA Prenduan, each dedication teacher has a different strategy in shaping the character of discipline and responsibility of students, because discipline and responsibility are excellence attitudes that are built on Islamic teachings and noble values of Indonesian culture. This study aims to examine the strategies implemented by the dedication teachers in shaping the discipline and responsibility character of UNIA Prenduan students, as well as to identify the challenges faced by the dedication teachers in this process. This research uses a qualitative approach with a case study design, where data is collected through interviews, observations, and documentation. The primary data sources are the dedication teachers for the 2024-2025 period. The results of this study indicate that the dedication teachers has different strategies in shaping the character of discipline and responsibility of students, including in terms of action strategies which include: enforcing regulations, supervision and approach to students, providing good examples, punishment and sanctions. As for the speech strategy, it includes: advice and motivation. The obstacles faced, namely from internal factors, include: no awareness from the students themselves, children who are difficult to manage and feel bored with the rules, differences in student’s backgrounds both in terms of emotional and life experiences. Meanwhile, external factors include: Some caretaker who violate the rules so that they set a bad example, time constraints and lack of totality of teachers in controlling so that students feel more free, and the influence from the bad friends